Impact of bariatric surgery on liver fibrosis indices among type 2 diabetes patients in a national cohort - Arsalan Seyedi; Soghra Rabizadeh; Sahar Karimpour Reyhan; Sara Hobaby; Samira Amin Afshari; Mostafa Shomalzadeh; Seyed Ali Nabipoorashrafi; Nasrin Asgari Soran; Amirhossein Yadegar; Fatemeh Mohammadi; Fatemeh Moosaei; Elahe Saffari; et al. (Scientific Reports)
Abstract Obesity is related to liver fibrosis, a condition marked by the collection of scar tissue in the liver due to the development of a profibrotic environment, which includes increased hepatocellular death and elevated reactive oxygen species production. The aim of study is to evaluate the effect of bariatric surgery on the association between liver fibrosis indices and obesity. This is a retrospective cohort, evaluating 1205 individuals diagnosed with type 2 diabetes (T2D) and living with obesity, who experienced bariatric surgery. These patients living with T2D and obesity were monitored after bariatric surgery for two years. The trajectory of biochemical markers and liver fibrosis indices were evaluated at five visits. These liver indices were Fibrosis-4 (FIB-4) index, aspartate aminotransferase (AST) to platelet ratio index, and non-alcoholic fatty liver disease (NAFLD) fibrosis score. FIB-4 index demonstrated notable trends based on its values. It showed an initial increase observed at the three-months visit, followed by a decline up to one year with a slight increase at the last follow-up (P-trend < 0.001). It should be mentioned that, mean FIB-4 in patients with FIB-4 ≥ 1.3 (pre-operation) did not exceed the value of 2.00, which is lower than the cut-off value of high risk for liver cirrhosis (FIB-4 ≥ 2.67). In addition, the NAFLD fibrosis score (NFS) demonstrated a substantial decline from − 0.32 ± 1.32 pre-operation to -0.86 ± 1.15 at the two-year mark (P-trend < 0.001). Finally, the AST to platelet ratio index (APRI) decreased from 0.27 ± 0.20 pre-operation to 0.23 ± 0.12 at the 12-month follow-up. Bariatric surgery significantly improves NFS and cause alterations in APRI and Fib-4 index levels without increasing the risk of liver cirrhosis development among patients with T2D and obesity.